Low density lipoprotein cholesterol phenotypes and their association with risk factors of cardiovascular disease among subjects attending health screening at a public university in Malaysia - Mazalan, Norlianah (2019)
Background: Cardiovascular disease (CVD) is the leading cause of death in Malaysia. Dyslipidaemia, a component of both Metabolic Syndrome (MetS) and Framingham Risk Score (FRS), is an established CVD risk factor. However, approximately 50% of individuals with coronary artery disease (CAD) have normal lipid levels and only 30% of all myocardial infarctions can be rationalised on the basis of conventional lipid profile. Low density lipoprotein cholesterol (LDL) particle concentration and size are reported to be important CVD predictors. Individuals with small dense LDL particles are categorised as Pattern B and are at greater risk of developing CAD. This pilot study aimed to determine the prevalence of Pattern B lipoprotein profile and its association with risk factors of CVD, specifically MetS and FRS among selected Malaysian population. This cross-sectional study involving 380 apparently healthy subjects aged ≥ 30 years old who attended health screening at Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (FMHS, UPM). Recruitment was by convenience non-random sampling. Sociodemographic factors and clinical characteristics were recorded in the proforma after informed consent. Biochemical analyses on fasting samples (lipid profile, plasma glucose and LDL subfractions) were performed at the Chemical Pathology Laboratory, FMHS, UPM. Data analysis was done using IBM SPSS Statistic version 23.0 for Windows. This study outcomes showed that the prevalence of Pattern B and normolipidaemic Pattern B were 45% and 8.8%, respectively. There was significant association between all sociodemographic factors, clinical characteristics and biochemical parameters (except for ethnicity, waist circumference for females, total cholesterol and LDL) with type of lipoprotein profile pattern. Male gender and MetS are independent predictors of Pattern B. Age, ethnicity and Pattern B independently predict MetS. Independent predictors of FRS include gender, ethnicity, diastolic blood pressure and Pattern B.The similarity between the independent biochemical predictors of Pattern B, MetS and FRS include LDL1 and LDL3.As conclusion, the prevalence of Pattern B and normolipidaemic Pattern B is relatively high compared to previous studies. Being male with MetS independently predicted Pattern B. By performing LDL subfraction analysis, additional individuals at risk could be identified, that would be missed if their risk were predicted according to their FRS alone. Atherogenic normolipidaemia broadens the population at risk for a CVD event, as these at-risk individuals are not recognised and hence not included in the protective measures of primary CVD prevention.